The association of Neurofibromatosis Type 1 and lower urinary tract dysfunction in the paediatric population – A critical review of literature. Issue 3 (June 2020) - Gao, Bruce; DeCotiis, Keara; Bobrowski, Adam; Koyle, Martin; O'Kelly, Fardod
Summary: Introduction: Neurofibromatosis Type 1 (NF1) is an autosomal dominant, multisystem, neurocutaneous disorder. This condition has been associated with lower urinary tract dysfunction due to either direct genitourinary organ involvement or spinal cord compression. Based on current literature, there are no reviews examining the relationship between NF1 and lower urinary tract dysfunction (LUTD) in the paediatric population. Methods: A critical review of the literature was conducted using a systematic search of MEDLINE, PubMed and Embase yielding a total of 1285 manuscripts published up to 2019. Two independent reviewers selected studies for screening, eligibility and inclusion into the review. Following title, abstract and full-text review, 46 articles were analyzed. Results: Within these 46 articles, 79 cases were presented. The mean patient age at the time of presentation was 6.97 ± 9.19 years. The most common urologic presentations were irritative lower urinary tract symptoms (30%) and a newly discovered abdominopelvic mass (21%). Diagnostic investigations commonly demonstrated a retrovesical mass with direct invasion of the bladder in 58 cases (73%) and other genitourinary organ involvement in 39 cases (39%). Throughout the total case volume, LUTD was present in 49%. Pathology of malignancy was most commonly malignant peripheral nerve sheath tumour and rhabdomyosarcoma (20% and 14%, respectively). When indicated, surgical management of the lower urinary tract included both radical and partial cystectomy. Conservative management of urinary retention included clean intermittent catheterization (56%), suprapubic catheterization (22%), vesicostomy creation (11%) and mitrofanoff creation (11%). Conclusion: A complete urologic evaluation including clinical, radiologic, and possibly pathologic investigation is warranted and should be performed for both diagnosis and appropriate management of LUTD in patients with NF1.